PENERAPAN MODEL PEMBELAJARAN CORE UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN ION DAN pH LARUTAN GARAM - Nesa Nozari; Herdini Herdini; Asmadi M. Noer (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2020)
The research aims to improve student learning results on ion equilibrium and pH of salt solution in class XI IPA SMAN 6 Pekanbaru. This is an experimental study with a pretest-posttest design. The sample study was students of class XI IPA 2 as an experimental class and students in class XI IPA 1 as a control class. The experimental class is the class applied to the CORE learning model while the control class is not treated. The data analysis technique used is the t-test. Based on the results of the data analysis test, tcount> ttable is 9,03> 1.66, meaning that the application of CORE’s learning model can improve student learning achievement on the subject of ion equilibrium and pH of salt solution in class XI IPA 6 SMAN 6 Pekanbaru